2011
DOI: 10.1097/mbc.0b013e32834b8246
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the use of coagulation test panels

Abstract: Use of a coagulation panel [prothrombin time (PT), partial thromboplastin time (PTT), thrombin time (TT) and fibrinogen], intended for evaluation of bleeding, tripled over 6 years, out of proportion to admissions, surgery, or transfusions. To determine whether the panels were ordered appropriately, we classified 28,737 sets of panel results into groups followed by chart reviews to determine typical patient histories. In 39% of panels, PT/PTT was normal. Prolonged PT occurred in 33% of results, due to liver fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…1). A prior study indicated that most mixing study results in acute care adult patients fell into one of the three patterns: for prolonged PT only, VKD factor deficiency was most likely and that curve was used; for prolonged PT and aPTT, again VKD factor deficiency was most likely and that curve was used; and for prolonged aPTT only, single-factor deficiency was most likely and the average single-factor deficiency curve used [4]. If clinical history suggested otherwise a different curve could be selected.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1). A prior study indicated that most mixing study results in acute care adult patients fell into one of the three patterns: for prolonged PT only, VKD factor deficiency was most likely and that curve was used; for prolonged PT and aPTT, again VKD factor deficiency was most likely and that curve was used; and for prolonged aPTT only, single-factor deficiency was most likely and the average single-factor deficiency curve used [4]. If clinical history suggested otherwise a different curve could be selected.…”
Section: Discussionmentioning
confidence: 97%
“…On the basis of a prior study of hospitalized patients [4], we assumed results fell into one of the three patterns ( Fig. 1): normal PT with prolonged aPTT, prolonged PT with normal aPTT, or prolonged PT and aPTT.…”
Section: Interpretation Of Mixing Studiesmentioning
confidence: 99%
“…As an acute-phase reactant, fibrinogen, as well as CRP, provide added information that may lead to moreaggressive treatment to prevent cardiovascular diseases. 3 The reimbursement volume for this test increased 3.8-fold from 2000 through 2010.…”
Section: Tests Used For Triage and Risk Assessment Of Cardiovascular mentioning
confidence: 99%
“…3 Increasingly, the fibrinogen test is used with other cardiac risk markers to determine overall risk for cardiovascular disease. As an acute-phase reactant, fibrinogen, as well as CRP, provide added information that may lead to moreaggressive treatment to prevent cardiovascular diseases.…”
Section: Tests Used For Triage and Risk Assessment Of Cardiovascular mentioning
confidence: 99%
See 1 more Smart Citation